(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper aims to assess the self-care practices among athletes participating in different sports. Understanding the self-care behaviors and routines of sportspersons is crucial for optimizing their physical and mental well-being, performance, and overall quality of life. This study investigates various aspects of self-care, including physical, psychological, and emotional dimensions, and explores potential differences based on sport-specific demands and training regimens.